SUPERIORITY OF RHYTHMIC STABILIZATION AND MULLIGAN TAPING TO ISOMETRIC EXERCISE AND MULLIGAN TAPING COMBINATION FOR REDUCING SHOULDER DISABILITY IN SURFERS - Yudi Pramana Putra; M. Widnyana; A.A Eka Septian Utama; I Dewa Gede Alit Kamayoga (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Abstract— Shoulder disability is a condition where there is limitation in the shoulder region which causes the inability of the shoulder to carry out functional movements and is often found in the extreme and repetitive sports activities which involve the shoulder as the main movement maker during the sport. Shoulder disability often becomes serious injury for surfers when to do paddle movements, shoulder disability injury are often worse by less optimal interventions, so it need more efforts to solve shoulder problems more quickly and efficiently. In this study, the researchers will comparing the effectiveness of intervention PNF